The end for bird-scarers? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Years of research by the Ministry of Agriculture, Fisheries and Food (MAFF) in the UK could soon benefit farmers around the world. The research started when it was noted that certain species of pear tree produced buds that were unpalatable to a...